W meandrach akademickiej wspólnoty – (za)myślenie - Kromolicka, Barbara (Studia Edukacyjne, 2018)
The article presents socio-cultural changes which have been taking place in the academic environment as a result of the process of implemented higher education reform and social change undergoing in the society. The author discusses the process of a university transformation which, while subject to economic challenges, changes substantially the quality of the functioning of the academic community.